Предмет: Алгебра,
автор: milana567197
(х+2)^3+3х^2-11=(х+3)^3
Ответы
Автор ответа:
1
Ответ:
-2
Объяснение:
x³+6x²+12x+8+3x²-11=x³+9x²+27x+27
x³-x³+6x²+3x²-9x²+12x-27x+8-11-27=0
-15x-30=0
-15x=30
x= -2
Автор ответа:
1
(х+2)³+3х²-11=(х+3)³
х³+6х²+12х+8+3х²-11=х³+9х²+27х+27
12х-27х=30
-15х=30
х=-2
х³+6х²+12х+8+3х²-11=х³+9х²+27х+27
12х-27х=30
-15х=30
х=-2
Похожие вопросы
Предмет: Русский язык,
автор: onebrock6
Предмет: Математика,
автор: vladislavbidas
Предмет: Қазақ тiлi,
автор: footstylegg
Предмет: Математика,
автор: 1234567890592
Предмет: История,
автор: nemetovasofia